Values Orientation and Performance of Higher Education Institutions in Ilocos Sur, Philippines - Bajet, Nelson (JPAIR Institutional Research, 2017)
The Values Education Program identifies human dignity as the "supreme" and all-embracing value. As a spiritual being, man must cultivate a sense of spirituality in consonance with nature and respond to God in faith. As an intellectual being, man must constantly search for truth. As a moral being, man must cultivate sense of social responsibility in pursuit of the welfare of the family and the good of larger community to achieve economic efficiency. This study aimed to determine the values orientation and performance of the students of the Two-Year Technical Course specialized in Electrical Technology in the University of Northern Philippines and the Ilocos Sur Polytechnic State College, Philippines. The study made use of descriptive-normative method of research. The values orientations of the students were determined through questionnaires, while their performance was based on their skill performance test in building wiring installation. As a whole, UNP and ISPSC students had "satisfactory" level in values orientation. The respondents possess a "Very High" skill performance. Their performance was significantly influenced by their values orientation. The Office of Student Affairs (OSA) of UNP and ISPSC should conduct more lecture series in Values Education and should encourage greater students participation in religious activities to put up with higher level of values orientation.
Keywords: Values Education; Religious participation; Performance UNP; ISPSC